(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
This study examines the dynamics of economic growth in Kupang City in relation to poverty, the Human Development Index (HDI), and inflation, which have not shown consistent improvement, indicating that economic development has not fully translated into better welfare outcomes. The study aims (1) to describe the trend of economic growth in Kupang City and (2) to analyze the partial and simultaneous effects of poverty, HDI, and inflation on economic growth during 2007–2023. A quantitative approach was employed using secondary data from Statistics Indonesia (BPS) Kupang City. The data were analyzed through descriptive statistics and multiple linear regression using SPSS. The descriptive results show that economic growth fluctuated, reaching its highest level at 9.00% in 2007 and its lowest at -2.05% in 2020 due to the Covid-19 shock, before rising again to 3.93% in 2023; the electricity, gas, and water supply sector contributed 8.52% to GDP formation. The inferential results indicate that poverty has a negative but insignificant effect on economic growth, HDI has a negative and significant effect, and inflation has a positive but insignificant effect. Simultaneously, the three variables have a significant effect on economic growth in Kupang City. These findings highlight the need to strengthen human development, maintain price stability, and implement more effective poverty-reduction strategies to promote higher-quality economic growth